Small Business Tax Policy, Informality, and Tax Evasion Evidence from Georgia - Bruhn, Miriam (The World Bank, 2014)
Using a panel of administrative data and regression discontinuity analysis, this paper examines how the introduction of preferential tax regimes for Georgian micro and small businesses in 2010 affects formal firm creation and tax compliance. The results show that the new tax regime for micro businesses increased the number of newly registered formal firms by 18-30 percent below the eligibility threshold during the first year of the reform, but not in subsequent years. The analysis does not find an effect of the new tax regime for small businesses on formal firm creation in any year. Policy makers are often concerned about abuse risks stemming from differentiated tax treatment of micro and small businesses. The analysis in this paper reveals reduced tax compliance in 2010 around the micro business eligibility threshold, but does not find significant evidence of reduced compliance by Georgian firms in later years. The results also do not show any significant evidence of strategic sorting around the regime eligibility thresholds